From structural resilience to cell specification - Intermediate filaments as regulators of cell fate - Sjöqvist Marika; Antfolk Daniel; Suarez-Rodriguez Freddy; Sahlgren Cecilia (WILEY, 2022)
During the last decades intermediate filaments (IFs) have emerged as important regulators of cellular signaling events, ascribing IFs with functions beyond the structural support they provide. The organ and developmental stage-specific expression of IFs regulate cell differentiation within developing or remodeling tissues. Lack of IFs causes perturbed stem cell differentiation in vasculature, intestine, nervous system, and mammary gland, in transgenic mouse models. The aberrant cell fate decisions are caused by deregulation of different stem cell signaling pathways, such as Notch, Wnt, YAP/TAZ, and TGF beta. Mutations in genes coding for IFs cause an array of different diseases, many related to stem cell dysfunction, but the molecular mechanisms remain unresolved. Here, we provide a comprehensive overview of how IFs interact with and regulate the activity, localization and function of different signaling proteins in stem cells, and how the assembly state and PTM profile of IFs may affect these processes. Identifying when, where and how IFs and cell signaling congregate, will expand our understanding of IF-linked stem cell dysfunction during development and disease.